Expounding Al-Bukhārī’s Theological Debates on Hadith Pertaining to Bayt Al-Maqdis from His Tarājim Abwāb - Amran, Najah Nadiah; Daud, Burhan Che; Akmaluddin, Muhammad (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
Some researchers claim that Muslim scholars do not emphasize the importance of Bayt al-Maqdis as strongly as they do upon the two holy cities of Islam, Makkah and Madinah. Even when they do, their writings are mixed with weak and forged narrations. Additionally, their efforts aimed to strengthen the political position of certain caliphs. In the current regional situation, some Muslims radically and literally interpret the hadith out of context to support the liberation of Bayt al-Maqdis. They believe that participating in jihadi group is a noble effort, even if it involves suicide bombings. Based on these issues, this article explores the efforts of scholars in hadith scholarship related to Bayt al-Maqdis. Specifically, it examines the perspective of a prominent hadith scholar, Imam al-Bukhari, in his initiative to compile hadiths, which he placed in different chapters of his book al-Jāmi’ al-Ṣaḥīḥ. This study employs a library research approach involving content analysis. The findings of this study reveal that numerous Muslim scholars have contributed significantly to Islamic scholarship in Bayt al-Maqdis through writing and the dissemination of knowledge. Specifically, they compiled hadiths about Bayt al-Maqdis in certain books and chapters. Imam al-Bukhari documented 12 narrations related to Bayt al-Maqdis in 9 books and 13 chapters. This study selected one hadith that is almost identical but is placed under four different chapters. This illustrates the unique way a single narration, both textually and contextually, can explain the significance and position of Bayt al-Maqdis in Islam from diverse and interesting perspectives. This study recommends continuing the exploration of hadiths related to Bayt al-Maqdis to examine various other forms of Tarājim. This will help the Muslim community, in particular, to understand the hadith texts comprehensively while simultaneously refuting the argument that Islam neglects this third holy city.